PEMANFAATAN PEKARANGAN KELUARGA PETANI DI DESA PARA-LELE, KECAMATAN TATOARENG, KABUPATEN KEPULAUAN SANGIHE - Husni ., Lais; Paulus A. Pangemanan; Sherly G. Jocom (AGRI-SOSIOEKONOMI, 2017)
This study aims to identify the area of yard farmland owned by the farmers' families in the cultivation of vegetables and spices and to identify the amount of costs incurred by the family of farmers for the consumption of vegetables and spices in one month. This study was conducted for three months from the time of preparation to the preparation of the final research report.Activitiesbegin from September to November 2017. The data used are primary data and secondary data. Primary data obtained from the respondents through surveys, documentation, interviews using a list of questions that have been prepared first.Teknik sample used is purposive sampling technique with the number of samples of 30 respondents. With the provisions of the families of farmers who grow vegetables and spices as many as 15 respondent and farm families who do not grow vegetables and spices as many as 15 respondent. Then the data collected will be analyzed descriptively and presented in written form and table. Based on data analysis that has been collected, it is concluded that the area of yard area owned by family of farmers who grow vegetables and spices mostly located in the area between 100 m² - 120 m² whereas family of farmers who do not plant vegetables and spices mostly located in the area between 121 m² - 140 m². As for the cost of consumption of vegetables, both farming families who do not plant, the average cost of Rp 330,000- Rp 599,000. for the cost of spice consumption of both planting and non-planting farm families, the average cost of Rp 289,000 - Rp.576,000.